Three dimensional printed nanogenerators - Zhou, Xinran (2021)
In the dawn of energy crisis and rising challenges in powering distributed lowenergy portable devices, nanogenerators, a class of mechanical energy har-vesters is gaining increasing interest in fundamental research and commercialapplications. Nanogenerators harvest energy by transducing mechanicalenergy into electric energy, the performance is highly related to the mechani-cal and electrical properties of the materials and devices. A typical nan-ogenerator consists of a substrate, a functional triboelectric active layer,electrode, and separator, which overall built-up a three dimensional (3D)structure. 3D printing with its ability to form complex 3D structures possesscoveted advantages in the development of nanogenerators. In this review, weintroduce the importance of 3D structures for nanogenerators and explicitlydiscuss the different 3D printing methods and the ink formulation to tacklethe challenges in 3D structured nanogenerators. Additionally, the principleand application of 4D printing in nanogenerator fabrication are criticallyhighlighted.